Best practices for collaborative conservation philanthropy. Issue 10 (14th September 2022) - Sanderson, John; Alper, Richard; Barrack, Jordana; Byrd, Caroline; Glenn, Erik; Jespersen, Kristen; Kimple, Aaron; Knight, Heather; Konrad, Peter; Kowalski, Ted; Nezzie, Dave; Ortez, Kristina; et al.
Abstract: Collaborative conservation brings diverse stakeholders together to sustain healthy landscapes and strengthen communities. Organizations fostering collaborative conservation depend on philanthropy to advance collaborative conservation, while philanthropic organizations depend on these organizations to advance their missions. Both face challenges engaging with each other as they work toward shared goals, yet open dialogue about how funders and practitioners work together is rare. The authors of this paper represent equal numbers of funders and practitioners who, together, identified eight best practices that are practical, effective actions funders and practitioners can take to better achieve shared conservation goals. These eight best practices are: (1) collaborate, (2) nurture relationships, (3) invest in capacity, (4) plan well, implement well, (5) engage diversity, (6) support entrepreneurial spirit, (7) reduce burdens, and (8) tell our story. By centering around collaboration, relationships, and diversity, these best practices exemplify several growing and valuable trends in philanthropy that support collaborative conservation.